Tax Subsidy Disclosure and Local Economic Effects - DE SIMONE, LISA; LESTER, REBECCA; RAGHUNANDAN, ANEESH (Journal of Accounting Research, 2025)
ABSTRACT We examine if the effectiveness of business tax subsidies varies based on state disclosure laws. The prior accounting literature on government disclosure documents substantial variation in the quality of such disclosures, raising questions about their effectiveness for monitoring. State and local business subsidies for investment and employment have tripled in size over the past 30 years, but transparency problems inhibit clear assessments of whether subsidies achieve their intended outcomes. We examine both internal disclosure laws, which mandate subsidy reporting by the granting state agency to other state oversight agencies, and external disclosure laws, which mandate reporting to the public. We find positive effects of subsidies on local employment when subsidies are subject to internal disclosure laws; by implementing such regimes, governments could forego 1.2–1.7 subsequent subsidies per county, saving 419.0–593.5 million in aggregate. In contrast, we observe little effect of external disclosure, which we show is due to governments either substituting to other types of incentives or posting stale information that impedes public monitoring. We contribute to the government disclosure literature by demonstrating the real employment effects of internal government disclosures, and we provide policy‐relevant evidence about the conditions under which external disclosure regimes facilitate public monitoring.